Proyecto de factibilidad para la producción, envasado y comercialización de la miel de abeja nativa (Scaptotrigona postica) en la provincia de El Oro - Aguirre Zambrano, Fernando Ramiro (2015)
A feasibility study was proposed to determine the feasibility of establishing a small business for the production and marketing of honey bee native Scaptotrigona postica in the upper area of the province of El Oro, covering Atahualpa, Portovelo, Piñas and Zaruma cantons. The objectives were to: Conduct a market study to determine the supply and demand in the province of El Oro, structure the technical study to define the size and location, to carry out the technical and financial study to establish profitability, and disseminate the results to the inhabitants sector. The market study found that there was an offer of 481.92 liters, a claim 2 023.6 liters, and an unmet demand 1 442.6 liters; technical study the installation of 8 meliponaries 50 hives was established with an annual output of 2404 bottles of 600 ml, which will be located in the El Espino, Malvas parish, canton Zaruma, half an hour distant city Machala, main potential market; under the conditions proposed project profitable, with an NPV of 123 788.23, an IRR of 824% and a B / C ratio of 2.3. Keywords: feasibility study, native bee, honey production, packaging, marketing, province of El Oro.